Acoustic response analysis of periodic orthogonal stiffened composite sandwich structure with pyramidal truss cores. (March 2022) - Wang, Zhonglong; Fu, Tao; Li, Bin
This paper presents analytical studies on the sound transmission loss behavior of functionally graded carbon nanotube reinforced composite (FG-CNTRC) truss core sandwich structure plates subjected to plane sound wave excitation, wherein three different functionally graded patterns are introduced for the carbon nanotubes through the thickness direction of structures. The effective CNTs material properties for each type are determined by the extended rule of mixture and the governing equations are based on the first order shear deformation theory. The compatibility of displacements on the interface between the plate and the stiffeners is employed to derive the governing equation of each stiffener. By using the modal expansion approach and Rayleigh integral, the sound transmission loss is described analytically. Since no existing results of sound insulation can be found for such composite material plate structure, experimental measurements of composite stiffener sandwich plate which is composed of carbon fiber reinforced composite material are subsequently carried out to validate the theoretical model, and good agreement is achieved. Based on the developed theoretical model, the influences of the volume fractions of CNT, truss core type, distribution type of CNT, stiffener spacing, and truss core height on sound transmission loss are subsequently presented.